Participants in trade union-staged demonstrations: a cross-country comparison. (August 2016) - Andretta, Massimiliano; Bosi, Lorenzo; Porta, Donatella della
Drawing both on social movement studies and labour studies, this article investigates the kind of people who join trade union-staged marches during the current crisis, looking at the presence of (politicized) grievances, collective identity and the embeddedness of mobilization. Data were taken from surveys conducted during 13 marches organized by the main trade unions in five European countries. They show that participants in union-staged demonstrations in countries in which a corporatist model dominates and trade unions have a tradition of business unionism (Belgium and the Netherlands) are characterized by higher political trust, more moderate positions on the left–right continuum and stronger organizational ties. On the other hand, in countries in which unions are less institutionally recognized and with a tradition of oppositional unionism (Italy and Spain), participants in union-staged demonstrations are more mistrustful of politics, located more to the left and rely more upon informal social networks to mobilize. The United Kingdom falls between these two poles.